Knowledge representation model for resolving conflict situations in technological object - Butleris, Rimantas; Nemuraitė, Lina (Information & Media, 1995)
In this paper the technological object of partial unremitting type is analysed, it main structural and functional properties are detailed. The formal description of technological object is presented by using the structural-functional model (SF-model).The structural component of model describes the structural hierarchy of technological object, it components, the technological parameters and the set of relationships of these structural components. The classes of entrance and qualitative technological parameters are declarated and the properties of these classes are presented.The functional component of SF-model characterizes the functional-control processes of technological object. The description of conflict situation in the technological object, the principles of it analysis and the control decisions inference is presented.The semantic-productional network is proposed to represent the SF-model of technological object in the knowledge base of expert system. This network is composed of the specialized semantic network and semantic rules. The structural component of SF-model is represented by the specialized semantic network, while the functional dependencies of technological parameters are expressed by production rules.
Keywords: -